PENDIDIKAN ISLAM DI ARAB SAUDI - Raden Roro Dinul Qoyyimah; Suryati Suryati (CAPITALIS: JOURNAL OF SOCIAL SCIENCES, 2025)
Islamic Education in Saudi Arabia. Islamic education in Saudi Arabia has a central role in shaping the identity and values of Saudi Arabian society. The country has long been a center of Islamic educational activity, playing an important role in the spread and maintenance of Islamic teachings throughout the world. This article discusses several key aspects of Islamic education in Saudi Arabia, including educational structure, curriculum. The structure of Islamic education in Saudi Arabia consists of various levels, from primary education to tertiary level. Islamic schools teach religious knowledge, the Koran, hadith, and other religious studies. The Islamic education curriculum is directed at ensuring a deep understanding of Islamic teachings and fostering Islamic moral and ethical values in everyday life. Islamic education in Saudi Arabia has a significant impact on shaping the character and worldview of its people. Even though it continues to develop, challenges and debates continue to emerge along with efforts to align Islamic education with the demands of the modern era.